Peningkatan Pengelolaan Administrasi dan Pemahaman Teknologi Kepada Masyarakat Kampung Melalui Pemanfaatan Sistem Informasi Desa di Kampung Maribu, Distrik Sentani Barat, Kabupaten Jayapura - Liza Angriani; Abd. R. Dayat; Eren A. Budiman (JURNAL PENGABDIAN PAPUA, 2025)
Kampung Maribu is one of the 5 (five) villages included in the administrative area of the West Sentani District, Jayapura Regency. Based on the observations made, we found that the residents of Kampung Maribu do not yet have concrete data due to the lack of proper administrative management at the Kampung Office, both in terms of population data archiving and the absence of archives for reporting the use of village funds used to implement the village work program. Additionally, with the limited human resources working at the village office, there is a need to utilize technology in the form of a Village Information System. Therefore, the improvement of administrative management and technological understanding for the village community through the utilization of the Village Information System in Maribu Village, West Sentani District, Jayapura Regency needs to be carried out. The results obtained after the implementation of the Village Information System in Kampung Maribu are as follows: the level of understanding among the residents of Kampung Maribu has increased, as indicated by the questionnaire results showing an average increase in administrative service satisfaction by 70%. This is because SIMDES helps in archiving population records and correspondence documents more comprehensively and systematically. Because of the online nature of SIMDES, the system can be accessed from anywhere and at any time, so the community does not need to come to the Village Office to manage documents or report citizen complaints; they can simply access it through the portal and use the self-service features. The availability of the LAPAK page on SIMDES helps residents who want to promote the processed products they have made. The active use of SIMDES as a news information portal has been carried out by village officials or activities conducted by the relevant Department.